Combined Transoral and Endoscopic Approach for Total Maxillectomy: A Pioneering Report - Liu, Zhuofu; Yu, Huapeng; Wang, Dehui; Wang, Jingjing; Sun, Xicai; Liu, Juan (Journal of Neurological Surgery Part B: Skull Base, 2013)
Total maxillectomy is sometimes necessary especially for malignant tumors originating from the maxillary sinus. Here we describe a combined transoral and endoscopic approach for total maxillectomy for the treatment of malignant maxillary sinus tumors and evaluate its short-term outcome. This approach was evaluated in terms of the physiological function, aesthetic outcome, and complications. Six patients underwent the above-mentioned approach for resection of malignant maxillary sinus tumors from May 2010 to June 2011. This combined transoral and endoscopic approach includes five basic steps: total sphenoethmoidectomy, sublabial incision, incision of the frontal process of the maxilla, incision of the zygomaticomaxillary fissure, and hard palate osteotomy. All patients with malignant maxillary sinus tumors successfully underwent the planned total endoscopic maxillectomy without the need for facial incision or transfixion of the nasal septum; there were no significant complications. Five patients received preoperative radiation therapy. All patients were well and had no recurrence at follow-up from 13 to 27 months. The combined approach is feasible and can be performed in carefully selected patients. The benefit of the absence of facial incisions or transfixion of the nasal septum, potential improvement in hemostasis, and visual magnification may help to decrease the morbidity of traditional open approaches.
Keywords: total maxillectomy; combined transoral and endoscopic approach; malignant tumor; maxillary sinus; endoscopic technique